1982
DOI: 10.1113/jphysiol.1982.sp014259
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic innervation of the canine abdominal vena cava and the origin of cholinergic vasoconstrictor nerves

Abstract: SUMMARY1. The effects ofelectrical stimulation ofthe greater splanchnic nerve and the vagus nerve on the middle segment of the inferior vena cava (i.v.c.) were studied in anaesthetized and unilaterally or bilaterally adrenalectomized dogs. The vascular response of the segment was measured as the change in pressure of an intravascular cuff inserted into the lumen of the segment.2. Electrical stimulation of the greater splanchnic nerve of either side caused an increase in the tension ofthe vein with a delay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…This may account for the fact that the sympathetic nerves distribute widely to the whole vascular system, while the parasympathetic nerves distribute only to limited sites in the vertebrate vascular system. This view is consistent with our earlier observations of the dog venous system, which show that cholinergic excitatory innervation was localized in a group of veins: the portal, mesenteric and hepatic veins and the middle segment of the inferior vena cava (3,4,49,50). The innervation was detected, both in vitro and in vivo, as a cholinergic component in neurally evoked contractile responses, which was augmented by anticholinesterase treatment and blocked by atropine.…”
Section: The Hypothesis and Some Implicationssupporting
confidence: 80%
“…This may account for the fact that the sympathetic nerves distribute widely to the whole vascular system, while the parasympathetic nerves distribute only to limited sites in the vertebrate vascular system. This view is consistent with our earlier observations of the dog venous system, which show that cholinergic excitatory innervation was localized in a group of veins: the portal, mesenteric and hepatic veins and the middle segment of the inferior vena cava (3,4,49,50). The innervation was detected, both in vitro and in vivo, as a cholinergic component in neurally evoked contractile responses, which was augmented by anticholinesterase treatment and blocked by atropine.…”
Section: The Hypothesis and Some Implicationssupporting
confidence: 80%
“…These three veins are embryologically related to the digestive tube, being characterized by the presence of massive longitudinal muscles, spontaneous rhythmic contractile activity, as well as cholinergic excitatory innervation (1 4). Some evidences of the innervation ob tained by in vitro and in vivo experiments were reported (3,(5)(6)(7). Additional findings were reported by Uematsu et al (8).…”
supporting
confidence: 71%
“…By means of a special intravascular cuff, the active tension development of the vascular wall could be recorded quantitatively, while preserving blood flow. A cholinergic constrictor response was recorded when the greater splanchnic nerve, but not the vagus nerve, was electrically stimulated (16). The same result was obtained in the portal vein, and it was occasionally, although slightly, observed in the pulmonary vein (25).…”
Section: Proposed Hypothesissupporting
confidence: 49%
“…Nakazato et al (16) demonstrated that in in vivo experiments of dogs, stimulation of the greater splanchnic nerves, but not of the vagus nerve, evoked an atropinesensitive cholinergic response in tension recordings from the middle segment of IVC. Subsequently, a similar finding was observed in recordings from the portal vein (25).…”
Section: The Efferent Pathway Of the Cholinergic Innervationmentioning
confidence: 99%